Ethically Integrating AI in Occupational Therapy Education: Enhancing Learning and Practice for the Future. - Sadek, Amy; Gowette, Sabrina (Open Journal of Occupational Therapy (OJOT))
Artificial intelligence (AI) has been around since the 1950s and is gaining traction in higher education and among health care professions. In this era of technology, it is imperative we equip both educators and students to have tech centric skills to support learning, improve efficiency, and enhance skills. Faculty and students alike need to be able to understand the ethics behind using digital information, such as that from AI tools and sources. As educators and students become more reliant on technology, and specifically AI, it is imperative not to lose the human connection in education. Educators are an integral part of fostering a student's growth by encouraging discussions and reflective practice, and AI cannot take the place of such communication. Thus, the aim of this paper was to demonstrate how OT educators and students can use AI tools in both didactic and experiential education as a supplemental tool for teaching and learning through the lens of the AOTA Code of Ethics.